Alchemist with Scale - Weiland, Johannes (1800)
A bearded alchemist wearing a fur-trimmed top coat and cap is carefully weighing ingredients with a balance. On top of his table is an exotic carpet covered with papers, a copper pitcher, and ceramic jar. Resting on a simple wooden bench in front of the table is a large book and jug with blue glaze marks and glass. The painting's focus on the alchemist's measured actions seems to carry a message of weighted judgment.
Keywords: Alchemists; Alchemy; Alchemists in art